A Novel CDC42 Mutation in an 11-Year Old Child Manifesting as Syndromic Immunodeficiency, Autoinflammation, Hemophagocytic Lymphohistiocytosis, and Malignancy: A Case Report - Szczawinska-Poplonyk, Aleksandra; Ploski, Rafal; Bernatowska, Ewa; Pac, Malgorzata (Frontiers in Immunology, 2020)
Background. The CDC42 (Cell Division Cycle 42) gene product, a Cdc42 molecule, is a member of the family of small Rho GTPases, which are implicated in a broad spectrum of physiological functions in cell cycle regulation, including the establishing and the controlling of the cell actin cytoskeleton, vesicle trafficking, cell polarity, proliferation, motility, and migration, transcription activation, reactive oxygen species production, and tumorigenesis. The CDC42 gene mutations are associated with distinct clinical phenotypes characterized by neurodevelopmental, growth, hematological, and immunological disturbances. Case presentation. We report on a case of an 11-year-old boy with syndromic features, immunodeficiency, and autoinflammation who developed primary hemophagocytic lymphohistiocytosis and malignant lymphoproliferation. In this patient a novel heterozygous p.Cys81Tyr mutation in the CDC42 gene was found by whole exome sequencing. Conclusions. The Cdc42 molecule plays a pivotal role in cell cycle regulation and a wide array of tissue-specific functions and its deregulation may result in a broad spectrum of molecular and cellular dysfunctions, making patients with CDC42 gene mutations susceptible to infections, immune dysregulation, and malignancy. In the patient studied, a syndromic phenotype with facial dysmorphism, neurodevelopmental delay, immunodeficiency, autoinflammation, hemophagocytic lymphohistiocytosis shares common features with Takenouchi-Kosaki syndrome and with C-terminal variants in CDC42. It is important to emphasize, that Hodgkin’s lymphoma is described for the first time in the medical literature in a pediatric patient with the novel p.Cys81Tyr mutation in the CDC42 gene. Further studies are required to delineate precisely the CDC42 genotype-phenotype correlations.